PENGARUH STRUKTUR AKTIVA, PERTUMBUHAN PENJUALAN, DIVIDEND PAYOUT RATIO, LIKUIDITAS DAN PROFITABILITAS TERHADAP STRUKTUR MODAL - Anantia Dewi Eviani (Universitas Slamet Riyadi, 2015)
The research purposed to identity and analyze the effect of tangibility assets, sales growth, dividend payout ratio, liquidity, and profitability on capital structure. Sampling was purposive sampling method, in order to obtain a sample of 33 manufactured companies listed on The Indonesia Stock Exchange in the year of 2011-2013. Data was used from the Indonesia Capital Market Directory (ICMD) and Financial Statements manufactured company. The analysis method of this research that used was multiple linear regressions analysis. The result showed that board of (1) tangibility assets did not have significant influence the capital structure, (2) sales growth has significant influence the capital structure, (3) dividend payout ratio has significant influence the capital structure, (4) liquidity has significant influence the capital structure (5) profitability has significant influence the capital structure. Keywords: capital structure, tangibility assets, sales growth, dividend payout ratio, liquidity, profitability